Characterization of native perennial ryegrasses for persistence in mediterranean rainfed conditions - Sanna, Federico; Franca, Antonello; Porqueddu, Claudio; Piluzza, Giovanna; Re, Giovanni A.; Sulas, Leonardo; Bullitta, Simonetta (Spanish Journal of Agricultural Research, 2014)
Forage varieties of Lolium perenne L. (perennial ryegrass) available on the seed market generally show low persistence in rainfed Mediterranean conditions. Eleven native populations of perennial ryegrass from Corsica and Sardinia, previously chosen for their ability to re-grow after summer drought, were grown in a 3-year field experiment in Sardinia (Italy). The objective was to characterize these populations for traits linked with persistence in rainfed conditions under low input management. Their differentiation and stability over time were assessed for some morphological traits (tiller, spike and flag leaf length, number of spikelets spike-1, spikelet and glume length). In addition, some agronomic traits (canopy height, dry matter and seed yield, spike emergence date) and physiological traits (canopy temperature and leaf area index) were observed to identify, using a multivariate approach, correlations with persistence. A significant variability between accessions was observed for all the morphological traits over the three years of observation; a significant Accession × Year interaction was found for tiller length, flag leaf length and number of spikelet/spike with a plastic adaptation to weather conditions of some populations, these traits being the most important contributors to persistence. The most persistent perennial ryegrass accession proved to be the most vigorous and early flowering one. Some contrasting accessions represent valuable resources to be exploited into breeding programs based on Mediterranean germplasm, in order to provide farmers with perennial ryegrass varieties adapted for different purposes and which are able to survive to more frequent hot and dry summer conditions in a context of climate change.